Seasonal cycle of orographic gravity wave occurrence above small islands in the Southern Hemisphere: Implications for effects on the general circulation. Issue 20 (28th October 2013) - Alexander, M. J.; Grimsdell, A. W.
<x xml:space="preserve">Abstract</x> [1] Orographic gravity waves generated by flow over the topography of small islands in the southern oceans have been observed from orbit with the Atmospheric Infrared Sounder on the Aqua satellite. We examine the occurrence frequencies of these waves in the stratosphere at ∼40km above 14 islands and examine geographical and seasonal changes. Our results show that these small island mountain waves occur commonly in the stratosphere in the May–September season, though not every day. Differing seasonal variations are evident at different islands, and the seasonal variations are closely related to latitude and prevailing wind patterns. We also examine interannual variability in 2years of data and the relationships between occurrence frequencies, momentum fluxes, and stratospheric and surface winds. The results suggest that stratospheric winds have a first‐order limiting effect on the observations of these island mountain waves in Atmospheric Infrared Sounder (AIRS) data. Surface wind direction and island orographic relief have an additional but secondary influence on the island mountain wave occurrence frequencies in AIRS data. The implications are that these wave events are extremely common and that on many days when the waves are not observed in AIRS data they have likely dissipated and induced a drag force on the atmosphere below the 40km observation level. Observations of momentum flux during these wave events also permit a first estimate of their importance to the general circulation of the Southern Hemisphere.